Thermal modelling and optimisation of total useful energy rate of Joule–Brayton reheat cogeneration cycle. Issue 2 (7th February 2016) - Dubey, M.; Chandra, H.; Kumar, Anil
Abstract : A thermal modelling for the performance evaluation of gas turbine cogeneration system with reheat is presented in this paper. The Joule–Brayton cogeneration reheat cycle is based on the total useful energy rate (TUER) has been optimised and the efficiency at the maximum TUER is determined. The variation of maximum dimensionless TUER and efficiency at maximum TUER with respect to cycle temperature ratio have also been analysed. From the results, it has been found that the dimensionless maximum TUER and the corresponding thermal efficiency decrease with the increase in power to heat ratio. The result also shows that the inclusion of reheat significantly improves the overall performance of the cycle. From the thermodynamic performance point of view, this methodology may be quite useful in the selection and comparison of combined energy production systems.